Floating production storage and offloading systems’ cost and motion performance: a systems thinking application - Whyte, Andrew; Nishanth, R.; Kurian, V. (HIGHER EDUCATION PRESS, 2018)
Floating production storage and offloading (FPSO) units increasingly represent a practical and economic means for deep-water oil extraction and production. Systems thinking gives a unique opportunity to seek a balance between FPSO technical performance(s), with whole-cost; stakeholder decision-making is charged to align different fit-for-use design specification options’ that address technical-motion(s), with respective life-cycle cost analyses (LCCA). Soft system methodology allows situation based analyses over set periods-of-time by diagnosing the problem-at-hand; namely, assessing the antecedents of life-cycle cost relative to FPSO sub-component design alternatives. Alternative mooring- component comparisons for either new-build hulls or refurbished hulls represent an initial necessary consideration to facilitate extraction, production and storage of deep-water oil reserves. Coupled dynamic analysis has been performed to generate FPSO motion in six degrees of freedom using SESAM DeepC, while life-cycle cost analysis (LCAA) studies give net-present-value comparisons reflective of market conditions. A parametric study has been conducted by varying wave heights from 4 – 8 m to understand FPSO motion behavior in the presence of wind and current, as well as comparing the motions of turreted versus spread mooring design alternatives. LCCA data has been generated to compare the cost of such different mooring options/hull conditions over 10 and 25-year periods. Systems thinking has been used to explain the interaction of problem variables; resultantly this paper is able to identify explicit factors affecting the choice of FPSO configurations in terms of motion and whole-cost, toward assisting significantly with the front-end engineering design (FEED) phase of fit-for-purpose configured FPSOs, in waters off Malaysia and Australia.